ANALISA KOREKSI FISKAL LAPORAN KEUANGAN PADA KONSULTAN PAJAK VAUDY STARWORLD & PARTNERS JAKARTA - Hartanti hartanti; Kenny T Fadjari (Universitas Bina Sarana Informatika, 2014)
Agency is one subject of income tax, to calculate the amount of income tax payable bookkeeping company must make customized with taxation legislation. Under article 4, paragraph 1 of Law No. 36 of 2008 which became the object of the tax is income, but in the application of tax accounting, recognition of expenses, require special accounting treatment. Underlying this issue is the tax accounting method differences between accounting and tax, it can not be separated with the time difference and the difference remains between accounting and fiscal. This research was conducted in order to determine the outcome of fiscal correction and its effect on the coorporate income tax calculations do Starworld Vaudy Tax Consulting & Patners Jakarta. The data obtained by observation, interviews, and documentation while an analytical technique used is descriptive qualitative analysis. The results of his research is the amount of taxable income according to the calculations of different companies after analysis of the financial statements of the fiscal correction, according to the company (before analysis) taxable income of Rp. 573.014.00 , while income taxation under the Act (after analysis) of Rp. 576. 740. 000, the difference to give effect to article 29 of income tax to be paid, according to the company (before analysis) of Rp.16.900.509, while according to the Tax Act (after analysis) of Rp.17.400.551, there is a difference of Rp.500.042, accrued companies, as well as installments of income tax article 25 according to the company (before analysis ) of Rp. 3.491.709, while according to the Tax Act (after analysis) of Rp. 3.533.379, For the company to be more careful in making reconciliation / correction adjusted fiscal Regulation Legislation Taxation Key words: Fiscal corection, PPh for Company